Classification of an equine skull in the Science Museum of Coimbra, Portugal, by means of multivariate and qualitative analysis - Pere M. Parés-Casanova; Mireia Torrent; Nuno Carolino; Joana Cabral-Oliveira (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2021)
The study aimed at classifying an equine skull stored in Museu da Ciência da Universidade de Coimbra, Coimbra (Portugal) on the basis of its morphology using multivariate analyses. A visual appraisal had revealed that it was not from a horse. Nineteen cephalic measurements were obtained and compared with available data of horses of different groups (poneys, trait and saddle), equine hybrids, Przewalski’s horse (Equus przewalskii), wild and domestic asses, and quaggas (Equus quagga). Multivariate analysis plus head profile allowed us to assign the skull to a mare hinny -the hybrid between a jenny (female donkey) and a stallion (male horse). The research highlights the possibilities of categorization of equid skulls according to morphometry but with a need to consider qualitative traits, as head profiles. But more such studies are needed to be conducted to establish clearly differences between mules and hinnies, especially among sympatric populations.